PENGARUH MOTIVASI RASIONAL, MOTIVASI EMOSIONAL DAN HARGA DIRI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE PADA MAHASISWA UNIVERSITAS UDAYANA DIMODERASI OLEH GENDER - Calista, I Gusti Ayu Audy; Suparna, Gede (E-Jurnal Manajemen; Vol 4 No 5 (2015), 2015)
The purpose of this study was to determine the influence of motivation bagimana rationa, emotional motivation and self-esteem of the smartphone purchase decision on udayana university students and how gender roles in moderating . The data in this study , using path analysis to discuss the direct influence of rational motivation , emotional motivation to self-esteem and also a direct influence on purchasing decisions , this study accompanied Sobel test to determine the effect of indirect and interaction test ( MRA ) to determine how gender roles in moderating . The results showed that the rational motivation and emotional motivation significant positive effect on self-esteem and motivation are also rationa, emotional motivation and self-esteem significant positive effect on the smartphone purchase decisio. Results of the analysis showed that gender moderation able to moderate in other words there is no difference between men and women in the smartphone purchase decision. This study provides insight into the influence of rational motivation, emotional motivation and self-esteem of the smartphone purchase decision in moderation by gender through path analysis research methods , analysis and test interaction Sobel (MRA)
Keywords: Motivation Rational, Emotional Motivation, Self-Esteem, Purchasing Decisions and Gender